2002
DOI: 10.1161/hc1002.105133
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Hospital Mortality After Coronary Artery Bypass Surgery

Abstract: Background-Data are conflicting over whether women have higher mortality than men after coronary artery bypass graft (CABG) surgery. Younger but not older women hospitalized for acute myocardial infarction have higher in-hospital mortality rates than men. We hypothesized that younger women also have higher in-hospital mortality rates after CABG. Methods and Results-We studied 51 187 patients (30% women) included in the National Cardiovascular Network database who received CABG at 23 clinical centers between Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
2
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(79 citation statements)
references
References 39 publications
5
66
2
6
Order By: Relevance
“…Previous studies, for example, have shown that gender differences are most pronounced in younger age groups and diminish with increasing age [8]. Vaccarino et al [8] compared the outcomes between men and women after stratifying patients by age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, for example, have shown that gender differences are most pronounced in younger age groups and diminish with increasing age [8]. Vaccarino et al [8] compared the outcomes between men and women after stratifying patients by age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, for example, have shown that gender differences are most pronounced in younger age groups and diminish with increasing age [8]. Vaccarino et al [8] compared the outcomes between men and women after stratifying patients by age. Women <50 years of age were 3 times more likely to die than men (3.4 vs. 1.1%), and women aged 50–59 years were 2.4 times more likely to die than men (2.6 vs. 1.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in management and outcome between men and women with cardiovascular disease have been reported [1,2,3,4,5,6,7]. For example, using data from a Swedish national quality register, Glader et al [1] showed that women had a worse outcome following stroke after adjustment for other prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Existem outras condições de maior co-morbidade comparadas ao homem: insuficiência cardía-ca congestiva, mais angina classe IIIB/ IIIC de Braunwald e diabetes. Insuficiência renal é a maior complicação no pós-operatório nas mulheres 127 .…”
Section: Sexounclassified